2011
DOI: 10.1098/rsfs.2011.0026
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative contrast-enhanced ultrasound imaging: a review of sources of variability

Abstract: Ultrasound provides a valuable tool for medical diagnosis offering real-time imaging with excellent spatial resolution and low cost. The advent of microbubble contrast agents has provided the additional ability to obtain essential quantitative information relating to tissue vascularity, tissue perfusion and even endothelial wall function. This technique has shown great promise for diagnosis and monitoring in a wide range of clinical conditions such as cardiovascular diseases and cancer, with considerable poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
219
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(231 citation statements)
references
References 128 publications
1
219
2
Order By: Relevance
“…Micron-size encapsulated bubbles (radius < 10 lm) are used in diagnostic ultrasound imaging as contrast enhancing agents (de Jong, 1996;Ferrara et al, 2007;Goldberg et al, 2001;Tang et al, 2011). They generate subharmonic signals that are utilized for subharmonic imaging-imaging at frequencies half that of the excitation (Forsberg et al, 2000;Shankar et al, 1998;Shankar et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Micron-size encapsulated bubbles (radius < 10 lm) are used in diagnostic ultrasound imaging as contrast enhancing agents (de Jong, 1996;Ferrara et al, 2007;Goldberg et al, 2001;Tang et al, 2011). They generate subharmonic signals that are utilized for subharmonic imaging-imaging at frequencies half that of the excitation (Forsberg et al, 2000;Shankar et al, 1998;Shankar et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, contrast-enhanced ultrasound (CEUS) has made it possible to image and quantify neovascularisation in plaques as well as adventitial VV (Feinstein 2006). However, current quantification of contrast enhancement is significantly limited by spatially heterogeneous and patient-specific attenuation (Tang et al 2008(Tang et al , 2011. During a US scan, ultrasound echo from a target is affected by attenuation between the US transducer and the target.…”
Section: Introductionmentioning
confidence: 99%
“…Burns and Becher (2000) showed that at low PNP the echo from MB is proportional to transmitted US signal, while at larger PNP values the echo exhibits some additional frequency components. These additional frequency components are usually whole or fractional multiples (harmonics) of the excitation US frequency (Tang et al, 2011). It was also shown that attenuation depends on excitation US frequency (Goertz et al, 2007;Emmer et al, 2009;Tang, Eckersley, 2007;.…”
Section: Introductionmentioning
confidence: 99%